The Impact of Profitability, Leverage, and Tax Avoidance on Earnings Management in Consumer Goods Companies Listed on the Indonesia Stock Exchange - Theophilus Tan Ariel; Yanuar Dananjaya (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
This study analyzes the impact of profitability, leverage, and tax avoidance on earnings management in consumer goods companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2020. Data were collected using purposive sampling technique with a sample of 93 companies. Using multiple linear regression analysis, this study finds that profitability, leverage, and tax avoidance do not have a significant impact on earnings management either partially or simultaneously. These findings suggest that other factors not studied may play a greater role in earnings management practices in consumer goods companies.